THE PHILOSOPHICAL AND PSYCHOLOGICAL DIMENSION OF CREATIVITY AND CREATIVENESS - Skyba, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
Different aspects of the problem of creativity and creativeness have a long and rich history. Interest in the study of this phenomenon dates back to Antiquity and is associated with the mystery and mysticism of the creative process. The earliest scientific studies of creativity in global psychology are attributed to the works of the English scientist Francis Galton, who explored intellectual giftedness through statistical analysis of human performance outcomes. The works of J. Guilford, who introduced the concept of divergent thinking, are considered the starting point for scientific research in the psychology of creativity and experimental studies of creativeness. Contemporary interpretations of the essence of creativity emphasize its universal nature, acknowledging that creative qualities are inherent to all individuals. The aim and tasks are to explore the features of the philosophical and psychological dimensions of creativity and creativeness. Research methods are general scientific and specialized methods and approaches are employed to investigate the features of the philosophical and psychological dimensions of creativity and creativeness. Research results. Different researchers focus on various aspects of creativity, either emphasizing its individual components or constructing systems of interacting elements. Philosophers view creativity as an essence that simultaneously belongs to both the subject and the external world. The most important indicator of creativity is thinking, characterized by divergence, convergence, breadth of categorization, and the remoteness of associations, which reflects a tendency toward broad generalizations of phenomena that are not visibly connected by categorical links. Discussion. The discussion includes an analysis of the psychological and pedagogical characteristics specific to each age, emphasizing the need to consider these factors in the process of developing creativity as a personality trait. Particular attention is given to the potential of adolescence in fostering creativity, as this period coincides with the student years. Conclusions. A creative personality possesses a creative style of activity, which is based on a developed and systematic sequence of actions aimed at enhancing the ability to perceive uniqueness and novelty in any object and to produce original outcomes or results